PENURUNAN NYERI KEPALA PADA LANSIA DENGAN HIPERTENSI MENGGUNAKAN RELAKSASI AUTOGENIK DI KELURAHAN MERSI PURWOKERTO - Dwi Novitasari; Ikit Netra Wirakhmi (MEDIA ILMU KESEHATAN, 2018)
Background: Headache in the occipital region is the most common symptom of hypertension, caused by enhanchement intra-cranial pressure and vasoconstriction resulting in decreased perfusion of cerebral tissue. This causes insomnia, decreased concentration and decreased ability of daily living activity. Autogenic relaxation causes vasodilation and a calm emotional response that increases the response of the parasympathetic system. This modulation stimulus can decrease perception of headache. Objective: The aims of this study was to find out how the reduction of headache on hypertension before and after autogenic relaxation. Methods: The design of this research was pre experimental with one group pretest-postest design approach. The sample are 38 patients with hypertension who complained of headache in Mersi Purwokerto. Selection has been using purposive sampling. Measurement of head pain using visual analog scale. Data analysis using Wilcoxon test. Results: The mean headache before the autogenic relaxation technique was 5.24, and the mean headache after autogenic relaxation technique was 3.47, including the range of moderate pain. There was a significant difference between headache before and after the autogenic relaxation technique with p value: 0,000. Conclusion: Autogenic relaxation can be used by the elderly with hypertension to reduce headache. Keywords: Autogenic relaxation, headache, hypertension.